Mesurer l’acceptabilité sociale d’un projet minier : essai de modélisation du risque social en contexte québécois - Kristina Maud Bergeron (Éditions en environnement VertigO, 2015)
Social acceptability of mining projects is a major issue for the extractive industry. The literature considering social acceptability in connection with the mining world discusses a concept called the social licence to operate, as a way to avoid disturbance that could compromise extractive activities. This reductive vision is a transposition in the social world of mining projects establishment dynamics. Moreover, there are definitional and measurement difficulties associated with the notion of social acceptability itself. With the view of being useful to actors involved in real-life situations, we created an index that determines the risk for conflict development between a company and a local community during the first stages of mineral resources development, at the beginning of advanced exploration. It is applicable to the Province of Quebec. The model is based on an analytical description of the main determinants of conflicts, articulated around three structuring poles : affected community-ies, the company promoting the project, and the project itself in its natural environment. A questionnaire is used to qualify the communicational dynamics, and completes the evaluation of a given situation while giving space to perceptions. The identified variables are weighted and combined to get the social risk index. The index can be used by investors, mining companies, communities and governments. It facilitates the identification of aspects that can generate more social risk and the development of a stakeholder’s dialogue. This article reflects the interdisciplinary approach adopted for this project.